Dermatology in Public Health Environments A Comprehensive Textbook (Springer International Publishing, 2018)
This book provides a reference guide in the field of dermatology, presenting and discussing its interface with public health. Dermatological diseases are extremely common in populations around the globe, and the systematization of knowledge about these dermatoses and their relationships with different epidemiological factors may help us to understand the challenges that governments and private institutions face and must try to overcome in order to improve global health. Undergraduate and graduate students, dermatologists and general practitioners who study and / or work in the area will find scientific support in this book, which is intended as a reference work for dermatological practice and public health. The book has ten sections addressing carefully selected topics, including: 1. concepts in dermatoepidemiology and the international strategies in programs of Public Health; 2-6. the most significant skin diseases (including dermatology in tro pical medicine); 7. diseases that are not primarily dermatological, but have a high impact on public health and may have skin and mucosal manifestations; 8. a number of emerging issues in dermatology in public health; 9. clinical approaches (diagnosis and management) to common dermatological symptoms and 10. multidisciplinary approaches in dermatology. The editors have brought together authors with extensive experience in their respective fields in order to provide a reference book for those involved in or with an interest in the relationship between dermatology and public health.